1983
DOI: 10.1016/0010-2180(83)90135-9
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent flame propagation and combustion in spark ignition engines

Abstract: Pressure measurements synchronized with high-speed motion picture records of flame propagation have been made in a transparent piston engine. The data show that the initial expansion speed of the flame front is close to that of a laminar flame. As the flame expands, its speed rapidly accelerates to a quasi-steady value comparable with that of the turbulent velocity fluctuations in the unburned gas. During the quasi-steady propagation phase, a significant fraction of the gas behind the visible front is unburned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(75 citation statements)
references
References 22 publications
1
68
0
Order By: Relevance
“…It should be noted that this ratio remains nearly constant over most of the combustion event and this is a useful property because it simplifies the analysis [59].…”
Section: Turbulent Burning Velocitiesmentioning
confidence: 99%
“…It should be noted that this ratio remains nearly constant over most of the combustion event and this is a useful property because it simplifies the analysis [59].…”
Section: Turbulent Burning Velocitiesmentioning
confidence: 99%
“…The ratio between unburned to burned gas density is approximately constant throughout the combustion and close to a value of 4 and the mass fraction burned x b can be calculated according to Beretta et al (1983). The gas densities were obtained by Morley (2005) for the in-cylinder conditions at stoichiometric spark timing (4.8 bar, 550 K) and a ratio of  u / b =4.7 was calculated.…”
Section: A2 Mfb From Flame Imaging and Thermodynamic Analysismentioning
confidence: 95%
“…In previous engine research images of flames in cylinders showed a significant enflamed volume, but the pressure measurements were not accurate or sensitive enough to indicate the evolving flame kernels [21,15]. Therefore, optical investigation of combustion is preferred to pressure tracing at the early combustion stages.…”
Section: Visualisation Of Initial Flame Kernel Growth In Si Enginesmentioning
confidence: 99%
“…The first two stages are of high importance in terms of in-cylinder pressure development [12][13][14][15][16]. These four stages are influenced by: spark energy and duration [17]; spark plug design and orientation [18]; in-cylinder flow field [19]; cyclic cylinder charging [20]; in-cylinder composition [21]; and other related factors. A detailed literature survey on the effects of these parameters on the four stages of combustion appeared in [12].…”
Section: Flame Structure and Propagationmentioning
confidence: 99%
See 1 more Smart Citation